Parental Roles in Enhancing Children’s Emotional Intelligence: An Islamic Education Perspective in Caruban Village - Dwi Hariyanto (Civiliza Publishing, 2026)
The purpose of this study is to examine the role of parents in enhancing children’s emotional intelligence in Caruban Village, Kendal Regency, as well as to identify the supporting and inhibiting factors involved, and to explore the implications of parental roles in enhancing children’s emotional intelligence from the perspective of Islamic Religious Education. This study employs a qualitative approach using a case study design in Caruban Village. Informants consisted of parents and students selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. Data validity was tested through triangulation, member checking, and peer debriefing. The findings indicate that parental roles in enhancing children’s emotional intelligence encompass four main aspects: learning assistance, religious habituation, emotional role modeling, and empathetic communication. These roles contribute to the development of emotional regulation, motivation, empathy, and social skills in children. Supporting factors include parental cooperation and the habituation of religious values, while inhibiting factors stem from parents’ busyness and environmental influences. The implications of the findings suggest that optimal parental involvement fosters the positive development of children’s emotional intelligence.